A magyarországi romákról (Szociológiai Szemle, 2024)
The paper collates the general data of the representative surveys of Romas, Gypsies, conducted in the years 1971 and 1994. While stating the growth of the Roma population and the growth of their proportion within the entire population of the country between the two surveys (1971: 3%; 1994: 5%), we have also found that the completion of the primary school has become quite general among them, which means that the Romas are not illiterate any more, but their disadvantages in secondary and higher education do not seem to diminish. The housing conditions of Romas have significantly improved, however, their segregation continues to be quite significant. The situation is the worst in respect of employment, in 1971 the Gypsy and the total male population were employed more or less to an equal extent, there has been no demand for the labour power of Romas as a consequence of recession: two-thirds of them are unemployed, which is just the double of the national average.In the paper proposals are elaborated for the improvement of the position of Romas at school and in labour.